INTEGRASI ILMU SOSIAL DENGAN TEKS AGAMA DALAM PERSPEKTIF TAFSIR AL-QUR’AN - Rosadisastra, Andi (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
To reconnect the Islamic religious sciences with science world needed a multi-disciplinary group involving Islamic scholars want any worldly Muslim scholars. Koran can be a source of inspiration or a source of known science knowledge without having to be stuck on a wall of separation between the proclamation creator of the science of Islamic and non-Islamic. Interpretation is not just an attempt to read the text, but it should be a transformation efforts and solutions to social problems of life. It required a tool, namely the nature of philosophy or theory and social sciences related to the study of interpretation in question. Then the development of the concept of ?methodology sanctification Islam? is an attractive offer for the efforts to realize the interpretation of verses epistemology social, or can also be referred to as ?Integrative Epistemology Social Interpretation? (IESI). IESI can be used as a tool for social interpretation of the verses and it is a further development of integrative interpretation